PERAN ASBABUN NUZUL DALAM MEMAHAMI KAIDAH PENAFSIRAN AL-QUR’AN - Indra Kusdiana; Zaimmah; Nur Syafiqah Binti Nahlil; Abdurauf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the role of Asbabun Nuzul in understanding the principles of Qur’anic interpretation. This research uses a qualitative approach with a library research method. The data were collected from the Qur’an, tafsir books, Ulumul Qur’an books, academic books, and relevant scientific articles. The findings show that Asbabun Nuzul has an important position in the process of Qur’anic interpretation. It helps explain the background of revelation, clarify meaning, prevent interpretive errors, and connect the historical context with the universal message of the Qur’an. Asbabun Nuzul also plays an important role in understanding the principle of al-‘ibrah bi ‘umum al-lafz la bi khusus al-sabab, which means that the lesson is taken from the general wording of the verse, not only from the specific cause of revelation. Therefore, Asbabun Nuzul does not only function as historical information, but also as a methodological tool in tafsir. This study confirms that understanding Asbabun Nuzul is essential for developing Qur’anic interpretation that is systematic, contextual, scientific, and academically accountable.